(untitled) (Indonesian Economic Justice Review, 2024)
This paper examines Indonesia’s trade policy and its implications for economic justice, with a focus on the balance between global economic integration and the needs of local industries and vulnerable populations. As one of the largest economies in Southeast Asia, Indonesia has increasingly integrated into the global trading system through free trade agreements (FTAs), membership in the World Trade Organization (WTO), and bilateral trade partnerships. While these policies have spurred economic growth, they have also raised concerns about their impact on domestic industries, labor markets, and income inequality. The study critically analyzes key trade policies, including tariff reductions, foreign direct investment (FDI) incentives, and agricultural subsidies, evaluating their effect on sectors such as agriculture, manufacturing, and services. Using a combination of quantitative data and qualitative case studies, the paper explores how trade liberalization has affected the economic well-being of different segments of society, particularly the rural poor, smallholder farmers, and low-skilled workers. The findings suggest that while Indonesia’s trade policy has contributed to overall economic growth, it has also exacerbated inequalities, particularly in rural areas, due to the displacement of local industries and the influx of foreign products. The paper concludes by recommending policy adjustments that promote more inclusive trade practices, including strengthening protections for vulnerable sectors, improving labor standards, and ensuring that the benefits of trade are more equitably distributed.